2023
DOI: 10.1094/phyto-04-22-0128-r
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkable Expansion of Oligopeptide Transporter Genes in Rust Fungi (Pucciniales) Suggests a Specialization in Nutrient Acquisition for Obligate Biotrophy

Abstract: Nutrients acquisition by rust fungi during their biotrophic growth has been assigned to a few transporters expressed in haustorial infection structures. We performed a comparative genomic analysis of all transporter genes (hereafter termed transportome) classified according to the Transporter Classification Database (TCDB) focusing specifically on rust fungi (order Pucciniales) versus other species in the Dikarya. We also surveyed expression of transporter genes in the poplar rust fungus for which transcriptom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Previous studies utilizing comparative genomics information, gene expression data and signatures of diversifying selection uncovered protein families uniquely linked to pathogenic fungi, including rusts (Sperschneider et al ., 2014 ). Recently, a comparison of the total set of transporter genes in the order Pucciniales with other dikarya fungi revealed that the genomes of rusts show a global reduction in their repertoire of transporter genes (Guerillot et al ., 2023 ). However, a marked expansion of specific transporter gene families compared with other dikarya was found, specifically for oligopeptide transporters (OPT) and three families related with metal transport (Guerillot et al ., 2023 ).…”
Section: Recent Advancements In Our Understanding Of the P ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies utilizing comparative genomics information, gene expression data and signatures of diversifying selection uncovered protein families uniquely linked to pathogenic fungi, including rusts (Sperschneider et al ., 2014 ). Recently, a comparison of the total set of transporter genes in the order Pucciniales with other dikarya fungi revealed that the genomes of rusts show a global reduction in their repertoire of transporter genes (Guerillot et al ., 2023 ). However, a marked expansion of specific transporter gene families compared with other dikarya was found, specifically for oligopeptide transporters (OPT) and three families related with metal transport (Guerillot et al ., 2023 ).…”
Section: Recent Advancements In Our Understanding Of the P ...mentioning
confidence: 99%
“…Recently, a comparison of the total set of transporter genes in the order Pucciniales with other dikarya fungi revealed that the genomes of rusts show a global reduction in their repertoire of transporter genes (Guerillot et al ., 2023 ). However, a marked expansion of specific transporter gene families compared with other dikarya was found, specifically for oligopeptide transporters (OPT) and three families related with metal transport (Guerillot et al ., 2023 ). These findings may reflect rust specialties related with adaptation to biotrophy in terms of nutrient acquisition and control of metal homeostasis.…”
Section: Recent Advancements In Our Understanding Of the P ...mentioning
confidence: 99%